Evaluating membrane fouling potentials of dissolved organic matter in brackish water. (1st February 2019) - Park, Sanghun; Nam, Taewoo; You, Jeongyeop; Kim, Eun-Sik; Choi, Ilhwan; Park, Jongkwan; Cho, Kyung Hwa
Abstract: Isolating dissolved organic matter (DOM) is a preliminary step that improves the accuracy of its characterization. In this study, DOM in brackish water was clearly separated and evaluated by multiple characterization analyses. The sample was divided into three fractions by preparative high-performance liquid chromatography (preparative HPLC) according to molecular size. The homogeneity of each fraction was estimated by analytical size exclusion chromatography (SEC) and fluorescence excitation-emission matrix (FEEM). Pyrolysis gas chromatography-mass spectrometry (Py-GC/MS) and liquid chromatography-organic carbon detection (LC-OCD) were used to characterize the physicochemical properties of each fraction. Py-GC/MS revealed that Fraction 1 consisted of evenly distributed organic matter in order polysaccharides, proteins, polyhydroxy aromatics, lignins, and lipids. However, Fraction 2 was primarily composed of dominant lipids and low portion of proteins, and Fraction 3 was composed predominantly of lignins and lipids. The LC-OCD results showed that Fractions 1 and 2 had similar organic carbon (OC) compositions: a humic substance (ca. 37%), building blocks (ca. 10%), and neutrals (ca. 37%), whereas Fraction 3 contained a high proportion of neutrals (62%). In the fouling experiments, the distinct DOM characteristics in each fraction resulted in different declining flux behaviors, ranked as: Fraction 2 > Fraction 1 > Fraction 3. Graphical abstract: Image 1 Highlights: Brackish water DOM was fractionated by preparative HPLC. LC-OCD and Py-GC/MS evaluated the characteristics of brackish water DOM fractions. Effect of DOM characteristics affected to fouling potential in membrane filtration. The high proportion of lipids showed highest fouling potential.